2016
DOI: 10.1016/j.regsciurbeco.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Property tax delinquency and its spillover effects on nearby properties

Abstract: This paper investigates the impact of property tax delinquency on the sales price of nearby residential properties, an effect that we call the "delinquency discount". We use a sample of 34,500 home sales and the population of delinquent properties for Chicago, Illinois during the period 2010 to 2013. We focus on the delinquency discount for properties within the same census block. We also examine the effect of delinquency duration on neighboring properties, as this measures the level of their financial distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There is some recent work on property tax delinquency (e.g. Alm et al ., , ). The literature on property tax fraud is more anecdotal.…”
Section: Type Of Income Net Misreporting Percentage (%) Percentage Ofmentioning
confidence: 97%
“…There is some recent work on property tax delinquency (e.g. Alm et al ., , ). The literature on property tax fraud is more anecdotal.…”
Section: Type Of Income Net Misreporting Percentage (%) Percentage Ofmentioning
confidence: 97%
“…This is equivalent to a $6,600 discount on the sale of the average home in their data. Alm et al (2016) also found the influence of foreclosed properties within the Census block of a property sale to be much larger than tax delinquency: approximately, a 20% decrease in the sale price for every 1% increase in the foreclosure rate. 2 Whitaker and Fitzpatrick (2013) examined the interactive effect of tax delinquency, foreclosure, and property vacancy in Cleveland for property sales in 2010 and 2011.…”
Section: Previous Research On Distressed Propertiesmentioning
confidence: 95%
“…However, along with Alm et al (2016) and Whitaker and Fitzpatrick (2013), we believe that neighborhood decline and depressed market values of homes can occur separate from the foreclosure process. No less important, but significantly less studied, is the influence of property tax delinquent properties.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations